# How do you solve the following linear system: y = 6 - 2x , -x+y=1 ?

Jan 16, 2016

Complex linear systems can be solved in matrix form using Cramer's Rule. Simple ones like this one can be arranged according to their factors and solved algebraically.

#### Explanation:

Complex linear systems can be solved in matrix form using Cramer's Rule. Simple ones like this one can be arranged according to their factors and solved algebraically.

Arrange the equations so that the factors align, with all of the unknowns on one side:
y + 2x = 6
y − x = 1

Then algebraically combine them. You can use multiplicative factors to an entire equation if the coefficients are not already equal. In this case the 'y' coefficients are both '1', so we can simply subtract one equation from the other to get a single equation in only the 'x' variable.
y + 2x = 6
-(y − x = 1)
3x = 5 Solve for x: x = 5/3

Substitute this value back into one equation to solve for 'y', then use the other equation to check the final values for correctness.
y + 2(5/3) = 6 ; y + 10/3 = 6 ; y = 18/3 – 10/3 ; y = 8/3
CHECK:
y − x = 1 ; 8/3 – 5/3 = 1 ; 3/3 = 1 ; 1 = 1 CORRECT!